Contribution of ceramic technological approaches to the anthropology and archaeology of pre- and protohistoric societies = apport des approches technologiques de la céramique à l'anthropologie et a l'archéologie des sociétés pré et protohistoriques : proceedings the XVIII UISPP World Congress (4-9 June 2018, Paris, France), volume 12, session IV-3 - Giligny, François; Dolbunova, Ekaterina; Gomart, Louise; Livingstone-Smith, Alexandre; Méry, Sophie (UISPP proceedings series, 2021)
The reconstruction of the technical systems of ceramic production and of its 'chaâne opératoire' is a means of exploring certain social structures in time and space. Papers here highlight the contribution of technological approaches to ceramics, both in archaeology and in ethnology, to the analysis of pre- and protohistoric societies.